THEORETICAL APPROACH TO THE FORMATION OF TERMINOLOGY IN THE FIELD OF EVALUATING THE FINANCIAL CONDITION OF THE ORGANIZATION - Elena Zharikova; Tatiana Kulakovskaya (Вестник Северо-Кавказского федерального университета)
The article deals with the some problems of terminology in the field of financial stability, solvency, liquidity. 'ntercommunication and interdependence of these concepts is certain. The chart of dependence of financial stability is offeredfrom the internal and external environment of enterprise. Concepts are analysed on the criterion of time. Definiteness of intercommunications and interdependence of investigational concepts predetermines management processes by them and search of backlogs of improvement of the financial state of company.